A new closed-form solution for circular openings modeled by the Unified Strength Theory and radius-dependent Young’s modulus - Zhang, Changguang; Zhao, Junhai; Zhang, Qinghe; Hu, Xiangdong (Computers and geotechnics, 2012)
A new closed-form solution is presented for the stress and displacement distribution surrounding circular openings with finite external radii that are subject to uniform internal and external pressures under plane strain conditions. The specific solution for a deep circular tunnel in an infinite rock mass is also provided. It is assumed that the rock mass is elastic–brittle–plastic and governed by the Unified Strength Theory (UST). In the plastic zone, the radius-dependent Young’s modulus (RDM) model and a non-associated linear flow rule were adopted to establish the radial displacement solution. The new closed-form solution obtained in this paper is a series of results rather than one specific solution; hence, it is suitable for a wide range of rock masses and engineering structures. The traditional solutions, which are based on the Mohr–Coulomb failure criterion and the Generalized Twin Shear Stress yield criterion, can be categorized as special cases of this proposed solution. This new solution agrees reasonably well with the results of a borehole collapse test, a secondary development numerical simulation and an additional closed-form solution using the generalized non-linear Hoek–Brown failure criterion. Parametric studies were conducted to investigate the effects of intermediate principal stress, RDM and dilatancy on the results. It is shown herein that the effects of intermediate principal stress and dilatancy are significant; the RDM model is recommended as the optimum approach for calculating radial displacement and support pressure.